Changes in interfacial composition and structure of milk fat globules are crucial regulating lipid digestion in simulated in-vitro infant gastrointestinal digestion. (January 2023) - Sun, Yue; Ma, Shuaiyi; Liu, Yibo; Jia, Zhibin; Li, Xiaodong; Liu, Lu; Ma, Qian; Jean Eric-parfait Kouame, Kouadio; Li, Chunmei; Leng, Youbin; Jiang, Shilong
Abstract: The interfacial phospholipid and protein compositions of fat globule in human milk and three different infant formulas (F1: supplied with MFGM and OPO; F2: supplied with OPO and without MFGM; F3: supplied with MFGM and without OPO) were analyzed and compared, and the changes of interfacial composition and structure on their in-vitro infant gastrointestinal digestion were evaluated. The study from the interfacial properties of fat globule to illustrating the effect of interfacial composition and structure on lipolysis and proteolysis. The results showed that, both F1 and human milk had a similar interfacial phospholipid composition and higher sphingomyelin (SM) content. The interfacial protein composition of F1 was closer to human milk. F1 had the average particle size of 3.67 ± 0.12 μm and a phospholipid layer on the surface of triglyceride. Meanwhile, the relatively complete phospholipid ring structure in F1 could always be observed during gastric digestion, while was gradually destroyed during intestinal digestion. Moreover, F2 and F3 are significantly different from HM and F1 in composition and structure of fat globule. Although MFGM is added to commercial infant formula (F3), most MFGM still existed in the aqueous phase of emulsion in free form. Notable, F1 had similar in-vitro lipolysis and proteolysis properties to human milk. These results indicated that the simulation of human milk fat globule at the molecular level and structure feature was the key contributing to digestion behavior. Graphical abstract: Image 1 Highlights: The abundant phospholipid ring structure were observed in F1. F1 had sn-2 SFAs and OPO, which reduced the formation of calcium soap. HM had the highest lipolysis rate of 86.3%, followed by F1 (82.9%) after digestion. F1 had similar digestive properties to human milk and is superior to F2 and F3. The simulation of HM fat at the molecular and structure is key to effect digestion.